2008
DOI: 10.3382/ps.2007-00436
|View full text |Cite
|
Sign up to set email alerts
|

Acclimation to Heat During Incubation. 2. Embryo Composition and Residual Egg Yolk Sac Fatty Acid Profiles in Chicks

Abstract: The aim of the research was to evaluate embryo composition and changes in egg yolk fatty acid composition during embryonic development as a function of incubation temperature and age of breeders. Eggs obtained from a common breeder stock at 3 ages: 32 (younger), 42 (mid age), and 65 (older) wk were divided into 2 groups and placed into 2 incubators: the control and the second where eggs were heat-acclimated (HA) at 38.5 degrees C for 6 h daily from d 10 to 18 of incubation. Body composition of embryos and chic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…The weight and percentage of drymatter accumulation of embryos are closely related to the fatty acid composition of the yolk (Peebles et al, 1999). Thus, the yolk and its fatty acid content are essential for meeting the nutritional requirements of developing embryos (Yalcin et al, 2008). In this study, the yolk sac weight was significantly higher in AFB 1 -treated groups than those of the control birds.…”
Section: Discussionmentioning
confidence: 45%
“…The weight and percentage of drymatter accumulation of embryos are closely related to the fatty acid composition of the yolk (Peebles et al, 1999). Thus, the yolk and its fatty acid content are essential for meeting the nutritional requirements of developing embryos (Yalcin et al, 2008). In this study, the yolk sac weight was significantly higher in AFB 1 -treated groups than those of the control birds.…”
Section: Discussionmentioning
confidence: 45%
“…WINELAND et al (2006ab) and LEKSRISOMPONG et al (2007) reported that lower average weights of chicks and their organs after heat stimulation. Other researchers (YALÇIN et al, 2008) increased the incubation temperature to 38.5ºC for six hours per day from the 10 th to the 18 th day, and reported accelerated growth compared to the control group with greater chick weight. This effect was not observed by YALÇIN & SIEGEL (2003), who assessed the effects of higher temperature (39.00ºC).…”
Section: Resultsmentioning
confidence: 97%
“…The absorption and utilization of nutrients from the yolk sac by the embryo are affected by breeder age (Burnham et al, 2001;Nangsuay et al, 2011;Peebles et al, 2000;Yadgary, Cahaner, Kedar, & Uni, 2010;Yalcin et al, 2008). Nangsuay et al (2011) reported at hatch a higher absolute yolk sac absorption (16.6 vs. 12.6 g), yolk sac absorption percentage (84.4% vs. 78.8%) and a higher nutrient assimilation of dry yolk (+0.16 g/g of dry YFBM) in hatchlings of older flocks (53 weeks) compared to young flocks (29 weeks).…”
Section: Embryo Metabolismmentioning
confidence: 99%